Freestanding carbon-coated CNT/Sn(O2) coaxial sponges with enhanced lithium-ion storage capability. Issue 48 (25th November 2015) - Luo, Bin; Qiu, Tengfei; Wang, Bin; Hao, Long; Li, Xianglong; Cao, Anyuan; Zhi, Linjie
Abstract : A freestanding spongy coaxial tin-based nanoarchitecture has been developed with exceptional electrochemical characteristics for energy storage application. Abstract : Carbon-coated, carbon nanotube (CNT)/tin(oxide) spongy coaxial nanostructures, CNT/Sn(O2 )@C, with large areal mass loadings have been developed by employing a three-dimensional CNT sponge as a backbone. The freestanding spongy coaxial nano-architecture demonstrates exceptional electrochemical characteristics of tin-based anode materials with appropriate structural engineering for energy storage application.